Liquid-phase sintering of medical-grade P558 stainless steel using a new biocompatible eutectic additive - Ghaffari, Mohammad (2013)
One of the effective approaches to reduce residual pores in powder metallurgy parts is activated liquid-phase sintering process using proper additives. In this work, for the first time, a new biocompatible additive (Mn–11.5 wt.% Si, a eutectic alloy) is experimented for liquid-phase sintering of nanocrystalline/amorphous P558 stainless steel powders. It is realized that by increasing the sintering aid content and temperature, the density is effectively increased: a sharp densification progress when the sintering temperature increases from 1000 °C to 1050 °C and a slower densification rate when it exceeds 1050 °C. This preliminary study opens up the development of high-density medical-grade stainless steels produced by powder metallurgy, where suitable additives can lower sintering temperature and time, which is promising for retarding grain growth and commercial applications.